Case Report: Immune Checkpoint Inhibitor-Induced Exuberant Tumor Inflammation With Accelerated Clinical Deterioration in Metastatic Renal Cell Carcinoma - Gopalakrishnan, Dharmesh; Jain, Rohit K.; Herbst, Laurie; Sikorski, Marcus; Mandava, Silpa; Azabdaftari, Gissou; Xu, Bo; LeVea, Charles; Robillard, Kevin; Ernstoff, Marc S.; George, Saby (Frontiers in Oncology, 2021)
Immune checkpoint inhibitors (ICIs) have revolutionized cancer therapy. Nivolumab, an anti-PD-1 monoclonal antibody, markedly improved overall survival in advanced renal cell carcinoma. However, ICIs can rarely trigger massive inflammation, a phenomenon characterized by rapid acceleration in radiographic tumor growth, the mechanisms underlying which are largely unknown. We report three patients with metastatic RCC who experienced rapid radiographic progression and clinical deterioration following treatment with nivolumab. However, histological analysis revealed no viable cancer despite the evidence of radiological progression. Instead, extensive necrosis and lymphohistiocytic infiltration were noted, as described previously in patients with ICI-induced pseudoprogression. Based on these observations, we postulate that exuberant antitumor inflammatory responses may contribute to adverse clinical outcomes in some patients with ICI-induced radiographic progression. Prospective studies incorporating tumor biopsies may shed more light on this rare phenomenon.